UKRAINE, THE TURKIC WORLD,AND CENTRAL ASIA - FINKO, Anton (CENTRAL ASIA AND THE CAUCASUS, 2009)
From the very beginning the relations between Southern and Western Rus/Ukraine have been far from simple and can be best described as ambivalent. We all know that Rus as a political unit came into existence amid incessant clashes with nomadic Turkic tribes—Pechenegs (Becheneks), Torks (Uzes), and Polovtsians (Kumans or Kypchaks)—pressing in from the Asian steppes. The Kievan rulers were no “meek lambs” either: they destroyed the Kingdom of the Khazars, the state with Turkic ethnic roots. Prince Svyatoslav’s inroad in the 960s into their lands when he captured Sarkel and plundered Itil and Semender was a weighty contribution to the Khazars’ sad fate. The Povest’ vremennyh let Chronicle, a key work that shaped the Eastern Slavs’ idea of history, offers a detailed account of the unrelenting struggle against the Polovtsians, who as time went on became actively involved in the Rurikoviches’ dynastic squabbles between the “elder” and “alienated” princes. In the 1080s-1090s the Kypchak pressure on Rus reached its peak to become intolerable; Grand Duke of Kiev Vladimir Monomachus and his sons were forced to march into the steppes in 1103, 1109, 1111, and 1116. Anyone wishing to understand Ukrainian mentality should take into account that it was affected by the latent fear of the Turkic world instilled in the course of history and intensifying under pressure of the Ukrainians’ prolonged experience of armed conflicts with all sorts of Turks and the fiercest of them, the Crimean Khanate, dated to a later period. The legend of Polovtsian Khan Boniaka quoted by Mikhail Dragomanov and later by Mikhail Grushevskiy was borrowed from the medieval chronicles. Appropriated by Ukrainian folklore, it was registered in the 18th century as a story about a real historical figure who lived at the turn of the 12th century and who was transformed into a mystical supernatural being or even an evil spirit.2 Hostility alternated with periods of military and political partnership, while mutual cultural impact was inevitable. In 1223, Rus and the Polovtsians led by Yuri Konchakovich and Daniil Kobiakovich fought side by side on the River Kalka to oppose the Mongolian expansion. This is one of the most frequently used, yet by far the only example of their cooperation. It was cemented by close kinship between the Rurikoviches and the Polovtsian nobles. Over time, Eastern Slavic names—witness Vasily Polovchanin, Lavr Polovchanian, Gleb Tireevich, Yaropolk Tomzakovich, and Yuri Konchakovich and Daniil Kobiakovich already mentioned—gained popularity among the Turkic top crust.